Impact social rehabilitation program on quality of life of inmates with illicit drug use - Megah Andriany; Refonda Rias Anggiri (JKP (Jurnal Keperawatan Padjajaran))
Background: Inmates with illicit drug use have experienced various problems that affect their Quality of Life (QoL). The social rehabilitation program is expected to improve their QoL. Studies investigating the impact of social rehabilitation programs on QoL of inmates with drug abuse are limited.